Risk assessment of China-Pakistan Fiber Optic Project (CPFOP) in the light of Multi-Criteria Decision Making (MCDM). (April 2019) - Ali, Yousaf; Asees Awan, Muhammad; Bilal, Muhammad; Khan, Jehangir; Petrillo, Antonella; Ali Khan, Arshad
Abstract: The China-Pakistan Economic Corridor (CPEC) is considered as an excellent breakthrough for improving the economic and security situation in the region. The estimated worth of CPEC is 62$ billion which is comprising of 49 developmental projects. China-Pakistan Fiber Optic Project (CPFOP) is one of the core projects among these, which will deliver safe route of voice traffic between both countries. CPFOP is greatly beneficial in terms of enhanced security and revenue generation. Currently, Pakistan's international connectivity is via submarine cables. CPFOP will provide an alternative route for international telecom traffic and also assist in achieving the rapidly growing internet traffic demand in Pakistan. It is estimated that 17 million people will get benefit from this project. However, every project has some undesirable impacts. The aim of this research paper is twofold; 1st to trace out the pros and cons of CPFOP. 2ndly, performing a risk assessment of CPFOP by using Fuzzy VIKOR technique. This approach will help in prioritizing a list of failure modes of Fiber Optic Cable (FOC). Lastly, this paper will help authorities for optimizing and safeguarding national interest in the wake of CPFOP.